Batalhando por e entre estilos culturais : um estudo sobre práticas culturais ao redor da transgressão negociadas pelo personagem estatal magistrado em um contexto tardo-moderno - Cunha, Tiago Lorenzini (2021)
This word discusses the available cultural practices or attitudes around transgression and mediated by a judge as both a state character and a late-modern subject, to negotiate style, meaning and power, in terms of symbolic rewards and strategies in a macro-structural context. In this sense, by investigating the following question, why and how a judge as a public actor decides to become a late-modern subject that negotiates with a series of cultural attitudes around transgression, resignifying and transiting between modernist and post-modernist practices, we defend the need to revalue the term transgression and specific analyses of the so-called Cultural Criminology, in order to bring closer the reflections about state and cultural practices in a late-modern dimension. To materialize such work approach, we address two obstacles or criminological consequences that make it difficult the appreciation of cultural practices around transgression and played by a magistrate as a state actor at a late modern level, which are, the cultural positivist understanding and close to a radical criminological determinism of expressions such as culture and transgression in late modernity, as well as the understanding in which the a judge as a public character would have an absent or reduced human capacity to stage cultural practices around transgression in comparison with non-judge characters (late modern society). Therefore, as a main thesis, we investigate the existence of a battle for and in between cultural styles in the contemporary society and connected with the attitudes of a judge as a public actor, which is why, depending on the cultural style chosen by each judge character, their symbolic motivations and strategies for obtaining this or another style will continue to spin, according to each and different human choice. In this sense, being part of the late modernity society, a magistrate as a state character shares with the former a set of practices and meanings, but in different proportions and visual focuses. Thus, we theorize the different cultural practices around transgression in contrast with a judge as a public character and what we call the battle for and in between cultural styles from an exemplificative and not exhaustive list, the materialization of these cultural disputes in the present time, for example the parological and imperialist style, the contingent style, the style of edgework and anarchy and the style of genocide of an extreme and a fantastic transgression in late modernity (crimefrei).